Rekonstruksi Teori Efektivitas Hukum dalam Konteks Hukum Keluarga Islam: Antara Substansi Hukum, Penegak Hukum, dan Budaya Hukum - Miftahul Ishlahuddany (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The effectiveness of Islamic family law in Indonesia faces a gap between formal norms and social reality, as seen in child marriage, high divorce rates, and non-compliance with court decisions. Conventional legal effectiveness theories (Soekanto & Friedman) have not fully captured the spiritual character of Islamic law. This research employs a qualitative method with juridical-normative and sociological approaches, utilizing library research on legislation, court decisions, and relevant literature. This research reconstructs legal effectiveness theory by integrating the maqāṣid al-syarī'ah approach and three legal system elements: substance, structure, and legal culture. This reconstruction aims to create a more comprehensive concept of effectiveness that is responsive to the social realities of Indonesian Muslim society and oriented toward family welfare. The findings indicate that Islamic family law effectiveness is only achieved when legal substance is just, law enforcement officials are professional, and legal culture supports substantive justice values. This approach makes Islamic family law an adaptive, just, and syariah-aligned instrument for social transformation